LabEmbryoCam: An opensource phenotyping system for developing aquatic animals - Ziad Ibbini; Maria Bruning; Sakina Allili; Luke A Holmes; Ellen Tully; Jamie McCoy; Benjamin Larsen; Tony Wilson; Guy Ludford; Jack Barrett-Kelly; John I. Spicer; Oliver Tills (HardwareX)
Phenomics is the acquisition of high-dimensional data on an individual-wide scale and is proving transformational in areas of biological research related to human health including medicine and the crop sciences. However, more broadly, a lack of accessible transferrable technologies and research approaches is significantly hindering the uptake of phenomics, in contrast to molecular-omics for which transferrable technologies have been a significant enabler. Aquatic embryos are natural models for phenomics, due to their small size, taxonomic diversity, ecological relevance, and high levels of temporal, spatial and functional change. Here, we present LabEmbryoCam, an autonomous phenotyping platform for timelapse imaging of developing aquatic embryos cultured in a multiwell plate format, and while optimised for embryos, the instrument is extremely versatile. The LabEmbryoCam capitalises on 3D printing, single board computers, consumer electronics and stepper motor enabled motion. We combine these into a compact and modular laboratory insturment to provide X, Y and Z motion of a camera and lens, a web application streamlined for rapid setup of experiments, user email notifications and a humidification chamber to reduce evaporation over prolonged acquisitions. Downstream analyses are provided, enabling automated embryo segmentation, heartrate measurement, motion tracking, and energy proxy trait (EPT) measurement. The LabEmbryoCam is a scalable, and flexible laboratory instrument, that leverages embryonic and early life stage organisms to tackle key global challenges including biological sensitivity assessment, toxicological screening, but also to support broader engagement with the earliest stages of life.